2007
DOI: 10.1152/ajpregu.00161.2007
|View full text |Cite
|
Sign up to set email alerts
|

Control of breathing and adaptation to high altitude in the bar-headed goose

Abstract: The bar-headed goose flies over the Himalayan mountains on its migratory route between South and Central Asia, reaching altitudes of up to 9,000 m. We compared control of breathing in this species with that of low-altitude waterfowl by exposing birds to step decreases in inspired O(2) under both poikilocapnic and isocapnic conditions. Bar-headed geese breathed substantially more than both greylag geese and pekin ducks during severe environmental (poikilocapnic) hypoxia (5% inspired O(2)). This was entirely due… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
105
1
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 96 publications
(117 citation statements)
references
References 62 publications
10
105
1
1
Order By: Relevance
“…Instead, these results suggest a primary reliance on lipid catabolism during steady-state thermogenesis. The decline in RER appeared to be more gradual in the highland deer mice, but this result is difficult to interpret, as it may reflect an increased rate of carbohydrate oxidation at the onset of thermogenesis or ventilatory hypocapnia due to an enhanced hypoxic ventilatory response in highland deer mice (37,38). Nonetheless, all of the mice were apparently relying almost exclusively on lipid oxidation after 10 min of sustained thermogenesis ( Fig.…”
Section: Resultsmentioning
confidence: 94%
“…Instead, these results suggest a primary reliance on lipid catabolism during steady-state thermogenesis. The decline in RER appeared to be more gradual in the highland deer mice, but this result is difficult to interpret, as it may reflect an increased rate of carbohydrate oxidation at the onset of thermogenesis or ventilatory hypocapnia due to an enhanced hypoxic ventilatory response in highland deer mice (37,38). Nonetheless, all of the mice were apparently relying almost exclusively on lipid oxidation after 10 min of sustained thermogenesis ( Fig.…”
Section: Resultsmentioning
confidence: 94%
“…This species breeds on the high plateaus of central Asia and, remarkably, has been observed flying over the summit of Mt Everest (8850 m) during its fall migration to northeastern India (Swan, 1970). A number of physiological traits increase O 2 uptake, circulation and diffusion to contribute to the remarkable physiological performance of bar-headed geese in hypoxic conditions (Petschow et al, 1977;Perutz, 1983;Jessen et al, 1991;Scott and Milsom, 2007;Scott et al, 2009aScott et al, , b, 2011. Recently, Scott et al (2011) reported variation in cytochrome c oxidase (COX) enzyme kinetics between bar-headed geese and closely related lowland species.…”
Section: Hb Polymorphisms In Deer Micementioning
confidence: 99%
“…Incredibly, bar-headed geese sustain the 10 -20-fold increase in O 2 consumption rate that is necessary to fuel flapping flight (Ward et al 2002), despite the severe hypoxia at these elevations. The physiological basis for this elevated O 2 transport capacity is not completely understood, but it results in part from evolutionary changes that improve O 2 uptake and circulation during hypoxia (Petschow et al 1977;Jessen et al 1991;Scott & Milsom 2007). Much less is known about the flight muscle of this species, but theoretical modelling suggests that an enhanced capacity for O 2 diffusion from blood into muscle, which can be realized with increased muscle capillarity, should also improve O 2 transport in hypoxia (Scott & Milsom 2006).…”
Section: Introductionmentioning
confidence: 99%